Social bases of a human image in philosophy - N.A. Tereshchenko; T.M. Shatunova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2019)
The paper analyzes philosophical ontology, one of the most important directions of heterology, claiming the absence of a single basis of being, world, human, and philosophy. One of the modi of baseless philosophy is considering the image of a human as a baseless phenomenon. We suggested an inverse optics for consideration of the problem and put forward the thesis that baseless logic, as well as understanding of the human image as an expression of baselessness, is a consequence of the process of fragmentation of the human idea in philosophy due to the oblivion and disregard of the social essence of a human and the reduction of ideas about them to the phenomenon of “naked life”. The study is relevant, because it is necessary to develop an adequate attitude of the society to all risks of creating a baseless human image, which is perceived as the object of biopolitical views and corresponding practices (manipulations), as a simple biological resource. A number of arguments were provided in favor of the dependence of the philosophical image of a human on the social and historical reality, which is shown not only as unitary, but also as plural, polyphonic. This reality, accordingly, generates multiple images of cultural heroes, which (images) are reflected by different philosophical systems. The modern (contemporary) processes of proletarization and development of “proletarskost” as a form of fragmentation of an individual turning it from the social atom into something unclear with a lack of quality were given as an illustration for detection of real bases of the baseless image of a human. A human becomes the simplest and elementary form of the social matter with no essential social specificity. In this context, the very principle of humanity is questioned, and any form of living and non-living is perceived as a social one. As a result of the study, it was concluded that the problem of the totally baseless image of a human testifies to the limitation (death) of philosophy itself. The most important finding is the fact that a basis of the philosophical image of a human should be searched not in the distant past or even in the present, but in the future. This is the basis that comes to us as a solution. And it seems as a solution not only concerning the image of a human, but also regarding their being. Such a solution can be considered the basis for creating image of a human being. The obtained results are important both for the development of philosophical theory of humans and society and for practical opposition to the attempts to manipulate a human as a natural biological material.